Social normative beliefs and older adults’ volunteering – A daily diary study - Maria Wirth; M. Clara de Paula Couto; Paula Molina Sander; Klaus Rothermund (Current Research in Behavioral Sciences)
Older adults are faced with societal normative expectations that set standards for age-appropriate behavior. They supposedly align their behavior with what is socially expected of them to avoid backlash and disapproval. However, a link between societal norms and older adults’ behavior has not been established in previous studies. In a pre-registered daily diary study, we tested the link between the societal norm that older adults should contribute to the common good (i.e., social activation) and volunteering in everyday life in a sample of older adults (N = 78, 60 –85 years). We presented (fictitious) social consensus feedback indicating that a majority of society either agrees or disagrees with social activation and tested the effect of this consensus feedback on endorsing social activation and engaging in daily volunteering. Replicating previous studies, participants who were told that a majority agrees with social activation reported higher endorsement of social activation than those being told that a majority disagrees. Daily volunteering did not differ between social consensus groups. However, we found a significant relation between endorsement of social activation and daily volunteering for the agreement but not the disagreement group. This finding indicates that strongly endorsing social activation may be a prerequisite for societal appeals regarding older adults’ volunteering to become effective. Given the relatively low level of daily volunteering in our sample, these results warrant further investigation. Our findings offer important insights for initiatives promoting social participation among older adults.